Haemodynamic effects of salbutamol in patients with acute myocardial infarction and severe left ventricular dysfunction. - Timmis, A D (1979)
The haemodynamic effects of salbutamol infusions at rates of 10,20, and 40 micrograms/min were measured in 11 patients with acute myocardial infarction complicated by left ventricular failure. Four patients also had cardiogenic shock. Consistent increases were observed in cardiac outputs at all doses (up to 56% at 40 micrograms/min), while the mean systemic arterial pressure fell slightly (average 5 mm Hg), implying a reduction in peripheral vascular resistance. Changes in right atrial pressure and indirect left atrial pressure (measured as pulmonary artery end-diastolic pressure) were small and not significant. Analysis of data from individual patients showed that the greatest increment in cardiac output was reached at 10 micrograms/min in two cases, 20 microgram/min in three, and 40 micrograms/min in the remaining six. Heart rate at these doses increased by an average of only 10 beats/min. Salbutamol failed to reduce left ventricular filling pressure and cannot be recommended for the treatment of pulmonary oedema in acute myocardial infarction. The increase in cardiac output, however, was considerable, so that the drug may be important in the management of low-output states. This action is probably a result of peripheral arteriolar dilatation (itself a result of beta 2-adrenoreceptor stimulation) and is achieved with little alteration in the principal determinants of myocardial oxygen requirement.